Application of Neck Technetium Uptake of the Neck in Post-Operation PTC Patients for Detection of Forthcoming Iodine Ablation Response to Therapy - Farzanefar, Saeed; Nakhjavani, Manouchehr; Marzban, Mehraneh; Eftekhari, Mohammad; Albooyeh, Hajar; Naseri, Maryam; Abbasi, Mehrshad (Indian journal of surgery, 2022)
Thyroid remnant after thyroidectomy is a major predictor for future recurrence of thyroid cancers; for which assessment, the accuracy of imaging is not optimal. To evaluate the value of the technetium uptake in the neck compared with neck ultrasonography, this application is used to predict future recurrence of differentiated thyroid cancer (DTC). The neck technetium uptake (NTU) value was acquired 20 min after injection of 1 mCi technetium by a camera. Patients were scheduled for forthcoming iodine ablation. Baseline risk factors were collected. Patients were followed for 10.5 (7 to 12) months when the records of the whole body scan, thyroglobulin, anti-thyroglobulin, neck ultrasonography, and the history of repeated iodine and surgical treatments were collected. The correlation of NTU and recurrence were studied. Out of 73 participants, 63 patients completed the study with established recurrence status and a valid NTU assessment. Baseline lymph node invasion (34.6% vs 80.0%; all 41.9%), extra-thyroid extension (17.0% vs 50.0%; all 22.2%), and tumor size (2.3 ± 2.1 vs 5.2 ± 2.4; all 2.7 ± 2.4) were higher in patients with future recurrence. But the NTU was similar in subjects with and without recurrence (−0.2 ± 0.7 vs 1.7 ± 6.3; all 59 ± 5.3). NTU was significantly lower in subjects with surgeries more extensive than thyroidectomy ( P = 0.03). Recurrence cannot be predicted by NTU, but NTU may be used as a surrogate factor to determine the extent and completeness of the thyroidectomy surgery.